Spectrofluorimetric Determination of Fluoroquinolones by Fluorescence Quenching of 1,4-Dihydroxyanthraquinone - Xia, Qinghai; Yang, Yaling; Liu, Mousheng; Li, Yabin; Yang, Changzhe (Asian Journal of Chemistry, 2012)
A new, rapid, simple and sensitive method has been established based on the mechanism of fluorescence quenching for determining fluoroquinolones namely ofloxacin, norfloxacin, ciprofloxacin and gatifloxacin. The quenching was found to be very effective and appreciable. The experimental parameters affecting the fluorescence intensities were studied and optimized. Under optimal experimental conditions, the calibration curve was found to be linear between F0/F and the concentration with the range of 0.015-3.85, 0.021-4.04, 0.018-4.26 and 0.024-4.35 μg mL-1 for ofloxacin, norfloxacin, ciprofloxacin and gatifloxacin, respectively. The detection limit was 0.009 μg mL-1 (ofloxacin), 0.012 μg mL-1 (norfloxacin), 0.010 μg mL-1 (ciprofloxacin) and 0.016 μg mL-1 (gatifloxacin). The mechanism of the fluorescence quenching has been discussed. The binding constant and the number of binding sites were 7.11 × 106 L mol-1 and 1.77 (ofloxacin), 7.05 × 105 L mol-1 and 1.16 (norfloxacin), 4.76 × 105 L mol-1 and 0.94 (ciprofloxacin), 1.23 × 106 L mol-1 and 1.22 (gatifloxacin), respectively. The thermodynamic parameters were obtained from data at different temperatures, DH < 0, DS < 0 and the mean value DG < 0 (Table-3), the results showed that the reaction was spontaneous and the main binding force was van der Waals force. The method has been applied to the determination of pharmaceutical tablets with satisfactory results.